Pengaruh Kompetensi Dan Komitmen Terhadap Kinerja Guru Honorer - Vicky Achmad Zulfikar (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2019)
This study aims to determine the effect of competence and commitment on teacher performance. The important role of competence can be divided into four aspects namely Personality Competence, Pedagogical Competence, Professional Competence, and Social Competence. While commitment is divided into three parts, namely affective commitment, normative commitment and continuous commitment. The research method used is a verification method. The sample used was a private primary school honorary teacher in Bandung Regency. Data analysis techniques using path analysis. The results of the study prove there is an influence of competence and commitment to teacher performance by 83.3%.